Viability, implantation cost and conduction of strawberry out of soil in substrate in organic production system - Octaveus, Matthieu; Campos, Felipe Silva; Lima, Claudia Simone Madruga; Fey, Rubens (Revista de Ciências Agroveterinárias, 2023)
In the state of Paraná, strawberry farming is relevant, however, it is still an expanding market. Understanding and determining the main economic aspects related to cultivation becomes essential for the success of the enterprise. The objective of this study was to survey the main costs of establishment, management, and economic viability of organic strawberry farming in a soilless substrate system in Laranjeiras do Sul-PR. The study was conducted in the 2022 crop season and divided into three stages. The first stage involved a literature review of all aspects of organic strawberry farming in a soilless substrate system. The second stage consisted of a case study, and the third stage involved the analysis of production costs and economic viability of the crop. The total costs of managing and establishing a 250 m² greenhouse with 1800 strawberry plants reached R 39,147.00, with the most significant cost components being related to the structure, especially eucalyptus poles. The following financial viability indices were used: Net Present Value (NPV), Internal Rate of Return (IRR), and Discounted Payback Period. The results obtained indicate financial viability in production, as the NPV was R 69,509.88; the IRR was 57%; the profitability was R 25.097,00 per year in a 250 m² greenhouse, and the Payback Period was 1.6 years. Analyzing these indices confirms that the investment is viable and promising.